Cystoscopic-guided laser ablation of intramural ectopic ureters in a female cat - Nicole H Gibbs; Larry G Adams; Masahiro Murakami; Julie Commons; Sarah ML Steinbach (Journal of Feline Medicine and Surgery Open Reports, 2024)
Case summary An 8-month-old female spayed domestic shorthair cat was presented for chronic urinary incontinence (UI). Since being adopted 6 months earlier, the cat had a history of urine leakage during both activity and rest. Baseline blood work and urine culture showed no significant abnormalities and no evidence of a urinary tract infection. An abdominal CT with excretory urography followed by a focal urinary tract ultrasound revealed a suspected right intramural ectopic ureter (EU) and potential left EU. Cystoscopy confirmed bilateral intramural EUs. Cystoscopic-guided laser ablation (CLA) of both EUs was performed. The cat developed temporary urinary obstruction (UO) 36 h after the procedure, which was medically managed with prazosin and buprenorphine. Ultimately, the cat’s urinary signs completely resolved with no UI recognized after the procedure and the cat has remained continent during 18 months of follow-up. Relevance and novel information CLA of intramural EUs is routinely performed in dogs, but this technique has not been previously reported in cats with this condition. Although post-procedural urinary tract signs were initially present, the cat ultimately had an excellent outcome with resolution of UI after this procedure.